A cross-sectional study exploring community perspectives on the impacts of COVID-19 in Nunavut and recommendations for a Holistic Inuit Qaujimajatuqangit approach to emergency response - Zoha Rana; Meagan Leach; Gwen K. Healey Akearok; Jaylene Ukpatiku; Nmesoma Umenwofor-Nweze (International Journal of Circumpolar Health)
The goal of this study was to examine and address critical knowledge gaps and develop an understanding of both the positive and negative societal outcomes resulting from the public health measures associated with the COVID-19 pandemic in Nunavut and the interventions being undertaken to promote positive well-being. Data collection for this study included narrative, in-person interviews in Iqaluit, Rankin Inlet, Baker Lake, and Cambridge Bay between September 2022 and January 2023. A total of 70 participants were interviewed for this study. Community highlighted challenges, such as crowding and food insecurity, and concern for the collective wellbeing of the community. Strengths included financials supports, food sharing, and maintaining community connections over a distance. Recommendations included a focus on holistic health such as 1) public education and awareness about communicable disease, 2) financial supports, 3) housing, 4) access to healthcare, 5) focus on Inuit Qaujimajatuqangit, 6) mental-health and addiction supports, and 7) community spaces. Community members described both strengths and challenges they believe impacted their experiences and service delivery as well as recommendations for the future.